PENGARUH PROGRAM KECAKAPAN VOKASIONAL TERHADAP KREATIVITAS KULINER DI RUMAH KREATIF ISTANA SURGA KECAMATAN PERCUT SEI TUAN, MEDAN - Eniriat Saputri Fau; Silvia Mariah Handayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research was conducted with the aim of describing the implementation of the vocational skills program, the level of creativity of participants, and analyzing the effect of the vocational skills program on culinary creativity at the Istana Surga Creative House, Percut Sei Tuan District, Medan. The study population consisted of 100 local residents, while the sample size was 30 people (29 women and 1 man) selected using a purposive sampling technique based on the criteria of culinary vocational skills training participants aged 35-55 years. Data collection was conducted using a questionnaire that had been tested for validity and reliability. Data were analyzed through instrument testing (validity and reliability), classical assumption tests (normality and linearity tests), simple linear regression and t-tests. The research results show that a vocational skills program that includes training in basic culinary skills (such as understanding and following kitchen hygiene and sanitation standards, using simple kitchen utensils (stoves, knives, and blenders), reading and following simple recipes, applying kitchen safety principles, and developing discipline, precision, and timeliness when cooking) and specialized culinary skills (such as advanced cooking techniques such as baking, steaming, and sautéing; preparing and serving dishes, plating, and garnishing; creating recipes and menu innovations; flavor innovations; packaging and presentation; managing a culinary business; managing inventory; managing capital; and marketing strategies for food products both offline and online) has been proven effective in enhancing participants' culinary creativity. The calculated t-value of 16.305 > t-table 0.367 with a significance level of 0.000 < 0.05, and a beta value of 0.951, indicate a positive and significant effect between the vocational skills program and participants' culinary creativity at the Istana Surga Creative House.